Investigation on the changing law of magnetoelectric anomalies in variable temperature coal rocks - Xiaokun Zhao; Jun Ge; An Zhang; WenCai Wang (Results in Engineering)
The changing law of magnetoelectric anomalies in the metamorphic process of coal rock bodies is of great significance to the prediction and study of fire in hidden coal fields. For this reason, this paper reveals the changing law of magnetoelectric anomalies in metamorphic coal rock bodies through the study of pyrolysis characteristics, microcrystalline structural changes, and physical phase transfer of the coal rock bodies, based on the four coal samples with different metamorphic degrees, and captures and elucidates the thermal gravity (TG) curves and micro-thermogravimetric (DTG) curves of the coal. Thermolysis behavior and characteristics. The results show that the variation rule of electrical anomalies during the metamorphic process is small at the beginning of the process, the dielectric properties of the coal samples show a significant increase from T2 to T3, and the dielectric constant reaches its maximum value at the T4 temperature point. The X-ray diffraction test was used to comprehensively analyze the microcrystalline morphological parameters of the coal before and after heating. The results showed that the high temperature induced a denser stacking of the carbonaceous layers, which strengthened the van der Waals forces between the layers, shortened the aromatic layer spacing, enhanced the electronic coupling between the layers, and increased the dielectric constant of the coal, resulting in an increase in the dielectric loss as well as the tangent value of the dielectric loss, and a blockage of the charge transport pathway. Based on X-ray diffraction data from four coal and seven rock samples with different degrees of metamorphism, in-depth analyses were performed using JADE to identify multiple phases in the coal and rock samples using the Rietveld refinement program, and semi-quantitative compositional assessments of the phases were performed. The results indicate that the conversion of iron minerals to more magnetic ferromagnetic compounds such as hematite (Fe2O3) and magnetite (Fe3O4) enhances the magnetization of the coal, while decomposition and oxidation reactions during the warming of the rocks alter their ferromagnetic compound type and content.